Perfil do desenvolvimento neuropsicomotor de pré-escolares na educação pública municipal e fatores associados, em Feira de Santana, Bahia: estudo epidemiológico - Brito, Cileide Mascarenhas Lopes (2010)
The infant development is the gradual evolution motor, in the language, intellectual and in the social interactions. The delay in these functions is one relevant problem that may reverberate on the school performance and future perspectives of insertion on labor market. The objectives of this study were indentifying the prevalence and the factors associated suspected delay on the development in children by 4 and 5 years old. Epidemiologic study of crosssectional, with 438 mothers-children pairs registered on the infant municipal public education of Feira de Santana, Bahia, in 2009. It used the Denver’s test II for neuropsychomotor development evaluation of children and applied one interview to their mother. The sample was by conglomerate, with raffle of school units (primary units) and the children (secondary units). In the statistic analysis was applied the test of X² with confidence interval of 95%. The statistic program was the SPSS 9.0 and the R version 2.11.0. The prevalence of suspected delay on the neuropsychomotor development was 46,3%, with predominance in masculine sex (PR=1.43; IC 95%= 1.15- 1.78) and the five years old group (PR= 1.42; IC95%= 1.14- 1.77). In addition to these, the lack of prenatal assistance (PR= 1.41; IC95%=1.05-1.91), started prenatal with three or more months (PR= 1.25; IC95%=1.002-1.56) and alcohol consumption risk in gestation (PR= 1.55; IC95% =1.26-1.91) were identified how associated factors in the logistic regression analysis. The results suggest vigilance measures to health in gestation and accompaniment of children development, with intention to prevent or treat early the suspected delays of development.